Perbedaan Paradigma Pemikiran Ekonomi Islam Kontemporer dan Implikasinya Terhadap Penerapan Sistem Ekonomi Syariah Modern - Awalia, Nurhikma; Burhan, Nur Amaliah; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of contemporary Islamic economics demonstrates a significant diversity of paradigms of thought, particularly through three main schools of thought: Iqtishaduna (Muhmmad Baqir al-Sadr), which rejects Western economic theory and emphasizes distributional inequality; Mainstream (Chapra, Mannan, Siddiqi), which integrates conventional concepts with sharia values; and Alternative-Critical (Timur Kuran), which criticizes the lack of originality of the islamic system. This study aims to analyze the differences in the characteristics of these paradigms, their critical implications for the implementation of modern Islamic economics, and their values in the context of maqasid al-syariah. Using a descriptive-qualitative approach with a normative-empirical literature study, the analysis is carried out through paradigm mapping, critical evaluation, and transformational reconstruction based on the Qur’an, Hadith, and Islamic economic literature. The results show a gap between normative theory and formalistic practice in Islamic financial institutions, where the dominance of pragmatic approaches has not fully realized social justice. The study recommends a paradigm synthesis for the development of an applicable, inclusive, and sustainable Islamic economy.